Analysis of The Effect of Work Environment and Human Resource Aspects on Employee Performance Quality In Building Maintenance Work - Dicky Andrianto Saputra B; Muhammad Isradi (Eduvest - Journal of Universal Studies, 2026)
The rapid development of infrastructure in Indonesia has not been matched by adequate attention to building maintenance activities. Many buildings experience deterioration before reaching their intended service life due to weak maintenance management, particularly in terms of human resources (HR). Worker performance plays a crucial role in maintenance success and is influenced by various factors, including discipline, motivation, work environment, training, ability, and tools. This study aims to analyze the influence of HR aspects and the work environment on worker performance quality in building maintenance projects at PT. XYZ, as well as to evaluate the importance and performance levels of each indicator using a combined method. A quantitative approach was applied using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS 3.0 software. Additionally, Importance-Performance Analysis (IPA) was employed to identify improvement priorities. The results indicate that among the six variables, only discipline has a positive and significant impact on Worker Performance (path coefficient = 0.243; T = 2.026; P = 0.043). Other variables, including the Work Environment, were not statistically significant. Mediation analysis revealed an indirect effect of the Work Environment on Discipline and Motivation (coefficient = 0.281; T = 1.921; P = 0.055). Discipline is the most dominant factor in improving performance, while enhancing training and work environment remains essential as a long-term managerial strategy. IPA identified training-related indicators and supervisor motivation support as top priorities for improvement.